Assessing the quality of higher education:: Concepts and forms - Bululukov, Oleg; Dmitrievich Marushev, Anatolii; Vladimirovich Kubariev, Ivan; Anatoliivna Shumilo, Inesa (DIXI, 2021)
Introduction: For the educational world to achieve its existence and taste of creation and existence, there is always that need to promote and expect quality education, and this can only be realized through the analysis of its basic concept and formalities put in place. It is in this lane that an article and research is considered necessary.Purpose: To recognize the undeniable importance of creating a reliable and transparent system of accreditation of educational institutions, the introduction of an independent system of education quality assessment, by the way of scientific analysis and comparison. The subject matter of the article consists in the concepts and forms of the quality of higher education.Methodology: Based on the analysis of scientific points of view, the authors have suggested their own definition of the concepts of “quality of higher education” and “form of assessing the quality”. The classification of forms of assessing the quality of education has been provided and its procedural forms have been defined.Conclusions: The authors have formulated propositions for improving the accreditation process in Ukraine. It has been noted that the issues related to the process of providing education in Ukraine are currently under close attention of both state authorities and international experts and public organizations.
Keywords: Accreditation; educational process; forms of assessment; higher education